Wurtzite CuGaS2 with an in-situ-formed CuO layer photocatalyzes CO2 conversion to ethylene with high selectivity - Chakraborty, Subhajit; Das, Risov; Riyaz, Mohd; Das, Kousik; Singh, Ashutosh Kumar; Bagchi, Debabrata; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte chemie-international edition, 2023)
We present surface reconstruction-induced C-C coupling whereby CO2 is converted into ethylene. The wurtzite phase of CuGaS2. undergoes in situ surface reconstruction, leading to the formation of a thin CuO layer over the pristine catalyst, which facilitates selective conversion of CO2 to ethylene (C2H4). Upon illumination, the catalyst efficiently converts CO2 to C2H4 with 75.1 % selectivity (92.7 % selectivity in terms of R-electron) and a 20.6 mu mol g(-1) h(-1) evolution rate. Subsequent spectroscopic and microscopic studies supported by theoretical analysis revealed operando-generated Cu2+, with the assistance of existing Cu+, functioning as an anchor for the generated *CO and thereby facilitating C-C coupling. This study demonstrates strain-induced in situ surface reconstruction leading to heterojunction formation, which finetunes the oxidation state of Cu and modulates the CO2 reduction reaction pathway to selective formation of ethylene.
Keywords: C-C coupling; charge polarization; CO2 reduction; Photocatalysis